2009
DOI: 10.1177/112067210901900106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Complications of Combined Phacoemulsification and Vitrectomy for Eyes with Coexisting Cataract and Vitreoretinal Diseases

Abstract: Postoperative complications did not increase significantly in the combined phacoemulsification and vitreoretinal surgery. Combined vitreoretinal surgery and phacoemulsification with foldable IOL implantation is safe and effective in treating vitreoretinal abnormalities coexisting with cataract. Based on extensive experience with the combined procedure, the authors suggest that combined surgery is recommended in select patients having simultaneous vitreoretinal pathologic changes and cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…9 We had a severe inflammatory response in only two cases (3.8%), one of which ended up with 3601 posterior synaechiae and iris bombe. This is much less than the rate of severe inflammation of up to 6-7% reported in some of the other studies, 10,13 and may be due to a more stable anterior chamber when MICS precedes vitrectomy.…”
Section: Discussionmentioning
confidence: 40%
“…9 We had a severe inflammatory response in only two cases (3.8%), one of which ended up with 3601 posterior synaechiae and iris bombe. This is much less than the rate of severe inflammation of up to 6-7% reported in some of the other studies, 10,13 and may be due to a more stable anterior chamber when MICS precedes vitrectomy.…”
Section: Discussionmentioning
confidence: 40%
“…The most common postoperative complication of combined phacoemulsification and vitrectomy (ie, phacovitrectomy) is posterior capsule opacification (PCO). 1,2 Posterior capsule opacification can lead to a gradual decrease in the quality of vision and visual acuity postoperatively. It has been reported that in general, the PCO rates are lower with 23-gauge transconjunctival phacovitrectomy than with 20-gauge phacovitrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…These include faster visual recovery and patient satisfaction, no suture-related astigmatism, less postoperative inflammation, less conjunctival fibrosis, easier vitreous shaving, better access to the vitreous base, and more effective postoperative tamponade (Koenig et al, 1990;Pollack et al, 2004;Axer-Siegel et al, 2006;Mochizuki et al, 2006;Treumer et al, 2006;Demetriades et al, 2003;Wensheng et al, 2009). There are three ways to start this procedure.…”
Section: Combined Proceduresmentioning
confidence: 99%